Natural variation in plant telomere length is associated with flowering time. Issue 4 (28th January 2021) - Choi, Jae Young; Abdulkina, Liliia R; Yin, Jun; Chastukhina, Inna B; Lovell, John T; Agabekian, Inna A; Young, Pierce G; Razzaque, Samsad; Shippen, Dorothy E; Juenger, Thomas E; Shakirov, Eugene V; Purugganan, Michael D
Abstract: Telomeres are highly repetitive DNA sequences found at the ends of chromosomes that protect the chromosomes from deterioration duringcell division. Here, using whole-genome re-sequencing and terminal restriction fragment assays, we found substantial natural intraspecific variation in telomere length in Arabidopsis thaliana, rice ( Oryza sativa ), and maize ( Zea mays ). Genome-wide association study (GWAS) mapping in A. thaliana identified 13 regions with GWAS-significant associations underlying telomere length variation, including a region that harbors the telomerase reverse transcriptase ( TERT ) gene. Population genomic analysis provided evidence for a selective sweep at the TERT region associated with longer telomeres. We found that telomere length is negatively correlated with flowering time variation not only in A. thaliana, but also in maize and rice, indicating a link between life-history traits and chromosome integrity. Our results point to several possible reasons for this correlation, including the possibility that longer telomeres may be more adaptive in plants that have faster developmental rates (and therefore flower earlier). Our work suggests that chromosomal structure itself might be an adaptive trait associated with plant life-history strategies. Abstract : Telomere length is associated with flowering time variation in Arabidopsis, rice, and maize.